1957
DOI: 10.1021/ja01577a045
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Derivatives as Intermediates in Polar Reactions. VIII. Difluoromethylene in the Reaction of Chlorodifluoromethane with Sodium Methoxide1

Abstract: DIFLUOROMETHYLENE IN THE REACTION OF CHLORODIFLUOROMETHANE 5493 temperature was kept under 35' by external cooling. When the reaction became sluggish, more catalyst was added. Reduction was complete when a viscous yellow oil appeared and only a faint odor of nitrobenzene could be detected." Water was added and the mixture placed in an icesalt-bath. The yellow oil soon crystallized. The crude azoxybenzene was removed by rapid filtration. Some of the impurities oiled out leaving behind a yellow solid. The oil wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 0 publications
0
59
0
Order By: Relevance
“…It means that both active particles, i.e., carbanions and difluorocarbene are generated under PTC conditions. According to Hine et al [32,33] chlorodifluorocarbanion is not involved in alkaline hydrolysis of freon R-22. We found that it hydrolyzed (via difluorocarbene) when passed through a 50% aq.…”
Section: Resultsmentioning
confidence: 99%
“…It means that both active particles, i.e., carbanions and difluorocarbene are generated under PTC conditions. According to Hine et al [32,33] chlorodifluorocarbanion is not involved in alkaline hydrolysis of freon R-22. We found that it hydrolyzed (via difluorocarbene) when passed through a 50% aq.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of CH 3 OH (or CH 3 ONa), the mechanism for the formation of the orthoformate had been proposed by Hine and Porter [12], and been verified by Lee et al [13]. The Scheme 1.…”
Section: Reaction Mechanismmentioning
confidence: 85%
“…The reaction of CH 3 CH 2 CH 2 OH (1e) gave only small amount of 3e (Table 3, Entry 5). It was reported that the difluorocarbene was generated by the reaction of alkoxide and CHClF 2 (Scheme 7) [12]. In the cases of 1c, 1d and 1e, the alkoxide would not be formed efficiently due to the low acidity of alcohols compared with 1a and 1b.…”
Section: Reaction Of Various Alcohols With Chclfmentioning
confidence: 99%
See 1 more Smart Citation
“…The extract was washed with water, dried with sodium sulfate and evaporated to dryness. The residue was chromatographed on silica gel to give 9 (3.7 g, 108 %) as a foam containing small amounts of solvents; IR (CHCl3) cm-1 1788, 1720,1668; NMR (CDCl3) 5 (10) A solution of p-methylbenzyl chloroformate (3.4 g) in methylene chloride (2 ml) was added to a mixture of 9 (3.38 g), pyridine (3.6 ml) and methylene chloride (3 ml) at -20°C.…”
Section: -Carboxylate (9)mentioning
confidence: 99%